Perihippocampal failure after hippocampal-avoidance whole-brain radiotherapy in cancer patients with brain metastases - Li-Tsun Shieh, MD; Sung-Wei Lee, MD; Chia-Chun Chen, MD; Yi-Chia Ho, MD; Yu-Wen Wang, MD; Sheng-Yow Ho, MD, MS; Peeyush Goel. (Medicine, 2022)
Abstract. Perihippocampal failure is a rare clinical scenario in brain metastatic cancer patients following hippocampal-avoidance (HA) whole-brain radiotherapy (HA-WBRT). The clinical features have not been fully identified because clinical data on intracranial failure after HA-WBRT are limited. It is thus necessary to accumulate clinical data. We retrospectively analyzed cancer patients with brain metastases who were diagnosed between January 2014 and September 2020 at a regional referral hospital. The medical records of patients who underwent HA-WBRT were reviewed. The clinical features of intracranial recurrence were described. Dosimetry parameters were compared in terms of deviation from the recommended protocol of the Radiation Therapy Oncology Report 0933. Twenty-four eligible patients with brain metastases who underwent HA-WBRT were identified; 13 (54%) were male. Seventeen patients (71%) had lung cancer, 6 (25%) had breast cancer, and 1 (4%) had liver cancer. The median overall survival was 12 months. Three patients developed intracranial failure during clinical follow-up, and 2 relapsed with intracranial failure in the perihippocampal region at 13 and 22 months, respectively. The perihippocampal failure rate was about 8%. One patient with small cell lung cancer received HA-prophylactic cranial irradiation; the minimum and maximum doses to the hippocampi were 6.8 and 10.7 Gy, respectively. Another patient with brain metastases from lung adenocarcinoma received HA-WBRT; the minimum and maximum doses to the hippocampi were 5.4 and 10.6 Gy, respectively. We reported unusual cases of intracranial failure in the perihippocampal region following HA-WBRT. Perihippocampal failure could be attributed to an under-dose of radiation partially or be resulted from aggressiveness of cancer per se. Further research on this topic is encouraged.